2020
DOI: 10.1039/d0cp01013h
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced extraction of phenol from model oils using ionic liquids elucidated with neutron diffraction

Abstract: Aromatic cation ionic liquids (ILs) based on alkylpyridiniums are shown to be good phenol extractants from model oils (hexane/toluene).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…70 Similar features are observed in aprotic ILs containing N-alkylpyridinium cations, arising from anions associating equatorially around pyridinium cations. 71,72,73 In contrast to typical ionic liquid structure, there is very close anion-anion interaction in both PILs. The corresponding {SO4}-{SO4} associations (Figure 3, top, blue dashed and solid curves) closely resemble sulfate associations in 'neat' sulfuric acid (first shell at 4.6 Å, second one at 6.6-11 Å).…”
Section: Centre Of Mass Radial Distribution Functionsmentioning
confidence: 91%
“…70 Similar features are observed in aprotic ILs containing N-alkylpyridinium cations, arising from anions associating equatorially around pyridinium cations. 71,72,73 In contrast to typical ionic liquid structure, there is very close anion-anion interaction in both PILs. The corresponding {SO4}-{SO4} associations (Figure 3, top, blue dashed and solid curves) closely resemble sulfate associations in 'neat' sulfuric acid (first shell at 4.6 Å, second one at 6.6-11 Å).…”
Section: Centre Of Mass Radial Distribution Functionsmentioning
confidence: 91%
“…where [phenol] init and [phenol] f inal are, respectively, the initial and post extraction concentrations of phenol determined in the model oil phase. The results and a comparison with the data that were obtained for representative tetraalkylammonium chlorides (from Turner et al [29]) and from choline chloride are shown in Table 3. All of the salts tested showed good extraction of phenol from hexane, with greater than 87% removal while using 1 and 2.…”
Section: Extraction Of Phenol From Hexane and Toluenementioning
confidence: 86%
“…Examining data from the screening of extraction with a broad range of tetraalkylammonium halide salts ([NR 4 ]X, R = Me, Et, Pr, Bu, and X = Cl, Br, I) [29] and comparison with the literature, some clear trends in the impact of the different eutectic forming organic salts on phenol extraction are apparent. There is a need for a hard, basic anion (supporting phenol-OH hydrogen bond donation to the anion as a primary association mode [30,36]), and the extraction efficiency increases, in general, with increasing size of the N-alkyl substituents from Me-Bu, as seen for the [NR 4 ]I salts, where phenol extraction from hexane increased from 7% to 96%.…”
Section: Extraction Of Phenol From Hexane and Toluenementioning
confidence: 99%
See 1 more Smart Citation
“…The results above also provide explanations on why phenolic compounds with different hydroxyl groups present different extraction efficiencies during extraction from waste water by employing imidazolium-based ILs. [48][49][50] The extraction percentage for phenol generally exceeds 90%, while that for resorcinol is smaller than 60%. 48 Phenol resides mostly in the hydrophobic phase of the IL cation, but its H-bonding ability via -OH results in a small ratio of phenol remaining in the aqueous phase.…”
Section: Polymer Precursor -Il Template Spatial Correlation Analysismentioning
confidence: 99%